(untitled) (Research, Society and Development, 2022)
Due to its properties, bentonite clays have a wide range of applications, including in the industrial sector. An important application of clays takes place in the oil industry. The State of Paraíba has a great variety of these clays, however, the large-scale exploration resulted in a decrease in their quantity, which caused a great impact on their quality. Thus, the objective of this work is to compare two clays from Paraíba, in the municipality of Boa Vista, called Bofe and Chocolate, for use in water-based drilling fluids. Both clays were characterized by particle size analysis (AG), chemical analysis by x-ray fluorescence (EDX), x-ray diffraction (DRX), differential thermal and thermogravimetric analysis (DTA and TG) and cation exchange capacity (CTC) . Rheological properties were determined by measuring apparent viscosity, plastic viscosity and filtrate volume. The characterizations proved that the samples refer to bentonitic clays, in addition to presenting the characteristics of typical clays from the state of Paraíba. After a comparative study between the two clays, it was concluded that only Chocolate clay presents values of apparent viscosity and filtrate volume in accordance with Petrobras standards, while Bofe clay only meets the specifications of filtrate volume.